Art Event and Social Media as A Brand for Art Learning and Introducing Local Wisdom in Kindergarten - Wahyu Pratiwi; Joko Pamungkas (Journal of Innovation in Educational and Cultural Research, 2025)
The development of art in early childhood education is an important area to pay attention to. The existence of digital technology that can be used in the education field can help educators optimize art activities with local wisdom themes to maximize children's art learning. This research uses a qualitative approach. Data was collected through observation, interviews, and documentation. The research results show a close correlation between art events and efforts to preserve local wisdom. Local wisdom that is preserved includes extracurricular angklung, vocals with traditional song themes, and dances accompanied by traditional Javanese songs. Schools provide facilities for children to learn about various arts through school contributions to art competitions and events that amaze local wisdom. Schools also actively document every art activity on social media. Based on the research that has been done, it can be concluded that art events and social media are a brand of art learning and a bridge to introduce local wisdom. Social media containing various children's art events can also provide positive value for school institutions and increase the school's market value among the community.